Study of the ubiquitin-like fold in Sde2 - Datta, Sumanjit (IISERM, 2018)
Post translational modification by ubiquitin is one of the most studied form of protein modification in eukaryotes. Ubiquitin and ubiquitin like proteins/modifiers (UBL/ULMs) regulate various biological processes by covalently conjugating to proteins. Majority of UBLs have been attributed as a protein modifier like ubiquitin, there are notable exceptions to it as well. Hub1, a ubiquitin like protein regulates RNA splicing but is not involved in protein modification. Another example of ubiquitin like domain protein (UDP) is Sde2, which regulates intron specific pre-mRNA splicing in Schizosaccharomyces pombe. Previously it has been shown that Sde2 has a ubiquitin fold at its N-terminus and a predicted C-terminus rich in helices. Two deubiquitinating enzymes (DUBs) Ubp5 and Ubp15 cleave Sde2 at a conserved GG ̴KGG motif to generate Sde2 UBL and Sde2-C. Despite having low sequence similarity with ubiquitin, Sde2 N-terminus attains a ubiquitin fold and still gets recognized by Ubp5 and Ubp15. This lead to the first part of the study, where we tried to find out the specificity of this DUBs-Sde2 interaction, it seems that the whole UBL fold is necessary for its recognition by Ubp5 and Ubp15 and results in ubiquitin-like processing. Recent reports have elucidated the function of Sde2-C in regulation of RNA splicing in fission yeast and replication stress release factor in mammalian cells; but no significant function has been attributed to Sde2 UBL . We sought to find out the function of Sde2 UBL ; from our experiment we could see some higher molecular adducts Sde2 UBL suggesting a possible role in protein conjugation. Lastly, we hypothesized that presence of UBL fold in Sde2 could regulate its incorporation in the spliceosome but not for other splicing factors like Hub1.
Keywords: Ubiquitin like proteins; Growth and complementation assay; Plasmids and DNA techniques; Function of Sde2